Managing Customer Relations through Online Banking - Nagu, Vinay Kumar (Indian Journal of Marketing, 2012)
Marketing exchanges have shifted from transactions to relationships. Relationship marketing in retail banking is the activity done by banks to attract, interact and retain more profitable customers because most retail banks have both profitable and unprofitable customers. Retention of small number of customers (5 percent) yields 95 percent increase on the net present value. To gain competitive advantage, big companies are now moving to a new orientation which is termed as customer-centric orientation. Electronic banking refers to Internet banking. The Internet has had a great impact on electronic banking now, it can be done without any time and geographic remoteness. Consumers all over the world can easily access their accounts 24 hours a day, seven days a week. This provides many opportunities to banks as well as customers and the person using online banking is young, well educated, having a high level of income and a good job. A customer-centric firm is considered one, which has the capability to treat every customer individually and uniquely. The core of relationship marketing is to develop and maintain long-term relationship with customers rather than simply a series of discrete transactions. They noted that the guiding principle for the management is the customer’s lifetime value; firms must consider the entire relationship with the customers rather than calculate discrete transactions.